2019
DOI: 10.1080/17450101.2019.1611028
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of precarity among ‘new migrants’: exploring the worker–capital relation through mobilities and mobility power

Abstract: This article conceptualises the role of mobilities within precarious working and living conditions, drawing on qualitative analysis of interviews (n=52) and a policy seminar (n=50) in NorthEast England. It focuses on refugees, asylum seekers, and Eastern European EU migrants, as policy-constructed groups that have been identified as disproportionately concentrated in precarious work. The article develops three 'dynamics of precarity', defined as 'surplus', 'rooted', and 'hyper-flexible', to conceptualise disti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…It showed that international migration became more concentrated over time in central areas and that the majority of international migrants had arrived since 2001, in line with impact on centrally located GP practices and schools. This spatial concentration was linked to available and cheap housing stock in areas of high deprivation and existing networks of migrants, as found by others (Vickers et al, 2019, Sue et al, 2019, also Park and Burgess, 2019[1925). However, service providers regarded the 2011 Census as an outdated source.…”
Section: Understanding Local Level Spatial Distributionmentioning
confidence: 63%
See 3 more Smart Citations
“…It showed that international migration became more concentrated over time in central areas and that the majority of international migrants had arrived since 2001, in line with impact on centrally located GP practices and schools. This spatial concentration was linked to available and cheap housing stock in areas of high deprivation and existing networks of migrants, as found by others (Vickers et al, 2019, Sue et al, 2019, also Park and Burgess, 2019[1925). However, service providers regarded the 2011 Census as an outdated source.…”
Section: Understanding Local Level Spatial Distributionmentioning
confidence: 63%
“…This creation of exclusionary bordering, it is argued, has rationalised popular public anxiety and negative perceptions of migrants, raised public awareness of borders, reduced social solidarity and affected people's rights (Guentner et al, 2016;Lukes et al, 2018). This is further applied to political distinctions between categories of migrant where 'refugee' is portrayed as a more deserving category than 'migrant', even those moving because of poverty and environmental change (Jones, 2017), creating a hierarchical system of rights in migrant regimes (Crawley and Skleparis, 2018;Vickers et al, 2019). However, the process of category construction, the nature of the categories, or global border regimes are rarely problematized politically, instead the individual is emphasised (Crawley and Skleparis, 2018;Jones, 2017).…”
Section: Categorisation Citizenship and Exclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…This can be partially attributed to the widespread perception that migrants are much more "flexible" than nonmigrants (Rolfe, 2017b). In particular, recent migrants from East and Central Europe are often portrayed as "hyper-flexible" workers due to their precarious cyclical mobility and acceptance of variable landscapes of opportunity in the United Kingdom (Vickers et al, 2019).…”
Section: Introduction: Contested Temporal Vocabularies Of Flexibilitymentioning
confidence: 99%